HUBUNGAN POLA ASUH ORANGTUA DENGAN KEMANDIRIAN PERSONAL HYGIENE ANAK USIA PRASEKOLAH DI TKIT PERMATA MULIA DESA BANJARAGUNG KECAMATAN PURI KABUPATEN MOJOKERTO - Henny Vidya; Surya Mustikasari (Nurse and Health: Jurnal Keperawatan, 2018)
ABSTRACTBackground: Many preschool children are lacking in maintaining their personal hygiene so that this facilitates the occurrence of illness due to lack of maintaining personal hygiene such as worms or diarrhea. This happens because the child is still not able to do personal hygiene independently or still assisted by parents.Purpose: The purpose of the study was to analyze the relationship of parenting with the independence of personal hygiene of preschoolers.Method: The research design is correlational analytic with crossectional approach. The study population is All parents and preschool children in kindergarten Permata Mulia Banjaragung Mojokerto as much as 41 mother and child. The sample was taken by purposive sampling technique as many as 37 respondents. The research variables are parenting as an independent variable and personal hygiene independence as dependent variable. Data were collected by questionnaire instrument of self-care pattern and self-reliance of hygiene, then chi square test.Results: The result of the research shows that 15 of the respondents have adopted the democratic parenting of most of the autonomy of children in the self-supporting category as many as 8 respondents (53.3%). Of the 9 respondents who apply authoritarian parenting system there is 1 child (11.1%) who are independent and parents Applying permissive parenting pattern of most children belonging to self-reliant as many as 7 resondents (53.8%). Chi square test results obtained values ρ = 0, 023 and α = 0.05 so that ρ <α then there is a Relationship Pattern Parenting with Child Independence Level.Conclusion: There is no best parenting pattern but parents should be able to choose the appropriate parenting pattern in children according to the situation and condition of the child, which is expected later on children have good independence early. Key words: Parenting, Independence, Preschool.